Superabsorbent Polymers as a Tool for Sustainable Water Management in Semi-Arid Agriculture: A Case Study from the Upper Cheliff Plain, Algeria - Taibi, Hamida; Bouderbala, Abdelkader (Annals of Arid Zone, 2025)
Water scarcity presents a significant challenge to agriculture in Mediterranean regions, where semi-arid climates, irregular rainfall, and increasing water demand threaten crop productivity. Superabsorbent polymers (SAPs), or hydrogels, offer a promising solution by enhancing soil water retention and improving irrigation efficiency. This study evaluates the effect of potassium polyacrylate hydrogel on soil properties in Algeria’s Upper Cheliff plain, a semi-arid area experiencing declining rainfall and rising temperatures. A randomized block experiment was conducted to assess five hydrogel application rates (0 to 4 g per plant-1) under drip irrigation. Key soil parameters-moisture content, pH, temperature, and electrical conductivity (EC)-were monitored throughout the duration of the experiment. Results indicated that moderate hydrogel doses (1.75 to 2 g per plant-1) significantly increased soil water retention (up to 34.9%, compared to 27.93% in control plots). These doses also caused slight reductions in soil pH and helped stabilize soil temperature. Conversely, higher application rates yielded diminishing benefits and led to increased EC levels, suggesting a potential risk of soil salinity. Statistical analysis confirmed that treatment effects were significant (p<0.05), with the most favourable outcomes observed at moderate application levels. These findings underscore the potential of SAPs to mitigate water stress in Mediterranean agriculture. However, precise dosing is essential to maximize water savings while minimizing the risk of soil salinity. While this study focuses on soil responses to hydrogel application, future research will include data on tomato growth performance